2020
DOI: 10.1177/1049909120984390
|View full text |Cite
|
Sign up to set email alerts
|

Chaplain-Physician Interactions From the Chaplain’s Perspective: A Mixed Method Analysis

Abstract: Background: The value of healthcare chaplains to patient care is increasingly recognized. However, physicians’ understandings of the role of pastoral care have been reported to be poor, which have raised concerns about the quality of chaplain-physician interactions and their impact on patient care. These interactions, particularly from the perspective of the chaplain, have not been extensively investigated. Methods: An anonymous survey about the interactions of chaplains with physicians was sent to chaplains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One study identified an association between staff referrals for chaplain care and the religious/spiritual identity of the health professional (Galek et al, 2007). Physicians, too, may make chaplaincy referrals based on a (Gomez et al, 2020). Such assumptions may limit the receipt of care for those religiously unaffiliated or without a documented affiliation.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified an association between staff referrals for chaplain care and the religious/spiritual identity of the health professional (Galek et al, 2007). Physicians, too, may make chaplaincy referrals based on a (Gomez et al, 2020). Such assumptions may limit the receipt of care for those religiously unaffiliated or without a documented affiliation.…”
Section: Discussionmentioning
confidence: 99%
“…While prior efforts to demonstrate the beneficial aspects of chaplaincy (e.g., attempting to show increased patient ratings in hospital satisfaction scores) have been mixed ( Damen et al., 2020a , Damen et al., 2020b ; Marin et al., 2015 ), the present data suggest other sets of key benefits that chaplains can provide. Given the critical needs to document the benefits of chaplaincy ( Gomez et al., 2021 ; Wirpsa et al., 2019 ), the present data are thus valuable.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are critically important, since chaplains are often under-resourced and marginalized, and efforts to document the beneficial effects of chaplains are needed but have faced challenges and thus been limited and had mixed results. Chaplains perceive barriers from institutions, other staff, patients and chaplaincy itself ( Best et al., 2022 ), often seeing a disconnect between doctors and themselves, with the former unfamiliar with chaplains' roles, and often not seeing it as helpful ( Gomez et al., 2021 ); and 62% of chaplains feel they are infrequently integrated into medical team discussions ( Wirpsa et al., 2019 ). Even palliative care physicians, nurses and social workers, though broadly understanding what chaplains do, were rarely aware of chaplains' roles in assisting with treatment decision-making and communication among patients, families and medical teams, and caring for the medical team ( Damen et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Despite these efforts, instruction on patient spirituality targeting undergraduate or graduate medical trainees remain inadequate, 7,8 with pertinent content typically presented in courses addressing other topics such as palliative care or cultural competency or in elective courses, workshops, and/or selfdirected experiences. [3][4][5][6] Hospital chaplains have assumed larger and more visible roles in the clinical setting, providing supportive, spiritual, and pastoral care to patients, their families, and staff, [9][10][11][12] particularly during the recent COVID-19 pandemic. 13 Consequently, close observation of healthcare chaplains potentially offers an experientially based approach for introducing early trainees such as medical students to issues of spirituality in healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital chaplains have assumed larger and more visible roles in the clinical setting, providing supportive, spiritual, and pastoral care to patients, their families, and staff, 9-12 particularly during the recent COVID-19 pandemic. 13 Consequently, close observation of healthcare chaplains potentially offers an experientially based approach for introducing early trainees such as medical students to issues of spirituality in healthcare.…”
Section: Introductionmentioning
confidence: 99%